Alternative Energy Options for India—A Multi-criteria Decision Analysis to Rank Energy Alternatives using Analytic Hierarchy Process and Fuzzy Logic with an Emphasis to Distributed Generation. Issue 2 (1st March 2017) - Kulkarni, Sanjeev H.; Jirage, Bhairu J.; Anil, T.R.
ABSTRACT: Several studies have been performed in last many years as to which type of energy source would be suitable for extending energy access for remote rural areas. Energy planning using multi-criteria analysis has attracted the attention of decision makers for a long time. Multi-Criteria Decision Making (MCDM) techniques are attractive in problems having multiple and conflicting objectives. This article develops a methodological framework providing insights to suitability of multi-criteria techniques in the context of operation energy alternatives namely Central Grid/Grid Extension, Solar Home Systems and Microgrids in India. The model was built using the Analytic Hierarchy Process (AHP) with empirical data from various sources. Several parameters like generation cost, price, losses, reliability, capacity, availability, and constraints (geological/local) were investigated. Based on the scheme developed by Saaty—the AHP and Fuzzy Sets using MATLAB these multi-criteria are evaluated and compared. The analysis were carried out under two scenarios namely—environment and cost. Finally alternatives for energy generation were ranked based on the AHP and Fuzzy logic. The results indicate that MICROGRID is the ideal choice among the alternatives for energy generation in a decentralised way and is a possible solution for eliminating energy poverty.